CURRENT–VOLTAGE CHARACTERISTIC OF THE DIODE (Scientific journal of the Fergana State University, 2026)
This article presents a comprehensive analysis of the current–voltage (I–V) characteristic of semiconductor diodes. Using diffusion equations and appropriate boundary conditions, analytical expressions for carrier concentrations and current densities are derived for both thin- and thick-base approximations. Special attention is given to the role of thermal current, which is highly dependent on intrinsic carrier concentration and differs significantly between silicon- and germanium-based diodes. The study highlights the forward voltage shift of approximately 0.3–0.4 V between these diode types and explains the underlying physical mechanisms. The introduction of the injection coefficient through specific resistances of the base and emitter further refines the description of current flow. The results contribute to a deeper understanding of diode operation and provide a solid theoretical foundation for optimizing their performance in electronic applications.